2019
DOI: 10.2460/javma.254.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Entomological and sociobehavioral components of heartworm (Dirofilaria immitis) infection in two Florida communities with a high or low prevalence of dogs with heartworm infection

Abstract: OBJECTIVE To assess knowledge, attitudes, and practices regarding heartworms (Dirofilaria immitis) and mosquito vectors among residents (dog owners and non-dog owners) in 2 neighborhoods in Florida and to perform entomological surveys of mosquito species in these neighborhoods and identify mosquito species infected with heartworm. DESIGN Cross-sectional study. SAMPLE 2,572 mosquitoes and 96 residents of 2 northern Florida communities. PROCEDURES A 32-item questionnaire was orally administered to a convenience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Interestingly, a majority (68.8%) of owners in the present study reported current use of a HWCM, similar to other recent papers surveying dog owners in Oklahoma and Florida [26,45]. This high owner-reported prevalence of use contrasts with other data indicating that, even in areas where heartworm infection is common, only a minority of pet dogs receive a HWCM [46,47].…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, a majority (68.8%) of owners in the present study reported current use of a HWCM, similar to other recent papers surveying dog owners in Oklahoma and Florida [26,45]. This high owner-reported prevalence of use contrasts with other data indicating that, even in areas where heartworm infection is common, only a minority of pet dogs receive a HWCM [46,47].…”
Section: Discussionsupporting
confidence: 83%
“…aegypti as an efficient vector of D. immitis in dogs [80,81], and a study in Florida found Ae. aegypti infected with D. immitis [82]. Given that Ae.…”
Section: Discussionmentioning
confidence: 99%
“…However, hookworm, whipworm, or ascarid infections were still detected in some dogs reportedly receiving HWCM in the present study, perhaps due to the earlier detection afforded by antigen testing, the short (2-3 week) prepatent period of hookworm, and the fact that not all HWCMs are effective against whipworm or other intestinal nematodes [16,17,27,38]. For example, injectable products are not effective against either whipworm or ascarids, and are not FDA-label approved for efficacy against new hookworm infections beyond the time of initial administration [39,40]. Detection of nematode infections and other parasites in dogs reported to be receiving HWCMs in the present study indicates that regular testing is warranted for all dogs even when these medications are used.…”
Section: Discussionmentioning
confidence: 99%